Effects of increased positive end-expiratory pressure on intracranial pressure in acute respiratory distress syndrome: a protocol of a prospective physiological study. Issue 11 (15th November 2016) - Chen, Han; Xu, Ming; Yang, Yan-Lin; Chen, Kai; Xu, Jing-Qing; Zhang, Ying-Rui; Yu, Rong-Guo; Zhou, Jian-Xin
Abstract : Introduction: There are concerns that the use of positive end-expiratory pressure (PEEP) in patients with brain injury may potentially elevate intracranial pressure (ICP). However, the transmission of PEEP into the thoracic cavity depends on the properties of the lungs and the chest wall. When chest wall elastance is high, PEEP can significantly increase pleural pressure. In the present study, we investigate the different effects of PEEP on the pleural pressure and ICP in different respiratory mechanics. Methods and analysis: This study is a prospective, single-centre, physiological study in patients with severe brain injury. Patients with acute respiratory distress syndrome with ventricular drainage will be enrolled. An oesophageal balloon catheter will be inserted to measure oesophageal pressure. Patients will be sedated and paralysed; airway pressure and oesophageal pressure will be measured during end-inspiratory occlusion and end-expiratory occlusion. Elastance of the chest wall, the lungs and the respiratory system will be calculated at PEEP levels of 5, 10 and 15 cm H2 O. We will classify each patient based on the maximal ΔICP/ΔPEEP being above or below the median for the study population. 2 groups will thus be compared. Ethics and dissemination: The study protocol and consent forms were approved by the Institutional Review Board of Fujian Provincial Hospital. Study findings will be disseminated through peer-reviewed publications and conference presentations. Trial registration number: NCT02670733 ; pre-results.